Spaced mathematics practice improves test scores and reduces overconfidence. Issue 4 (9th March 2021) - Emeny, William G.; Hartwig, Marissa K.; Rohrer, Doug
Abstract: The practice assignments in a mathematics textbook or course can be arranged so that most of the problems relating to any particular concept are massed together in a single assignment, or these related problems can be distributed across many assignments–a format known as spaced practice. Here we report the results of two classroom experiments that assessed the effects of mathematics spacing on both test scores and students' predictions of their test scores. In each experiment, students in Year 7 (11–12 years of age) either massed their practice into a single session or divided their practice across three sessions spaced 1 week apart, followed 1 month later by a test. In both experiments, spaced practice produced higher test scores than did massed practice, and test score predictions were relatively accurate after spaced practice yet grossly overconfident after massed practice.